Bioaffinity Sensors: The Era of Digital Health: A Review of Portable and Wearable Affinity Biosensors (Adv. Funct. Mater. 29/2020). (16th July 2020) - Tu, Jiaobing; Torrente‐Rodríguez, Rebeca M.; Wang, Minqiang; Gao, Wei
Abstract : Mobile phone supported wireless sensing technologies in the medical field facilitate the monitoring and personalized management of diseases. In article number 1906713, Wei Gao and co‐workers present a comprehensive overview of the recent advances in portable and wearable mHealth devices. The key bottlenecks and opportunities for future wearable bioaffinity sensing systems are also discussed.